MOMEN AKUMULASI DARI SUATU ANUITAS AWAL DENGAN TINGKAT BUNGA ACAK - Ari Fatmawati; Johannes Kho; Aziskhan ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article discusses the three moments formed from the accumulation of due annuitywith random interest rate. The highest moment of these three moments is obtained byfirst determining the previous two moments. Moment accumulation is used to predictthe accumulation of profits expected by investors from an investment made during nperiods.